Fibroblast Growth Factor-23-Klotho Axis in Cardiorenal Syndrome: Mediators and Potential Therapeutic Targets - Navarro-García, José Alberto; González-Lafuente, Laura; Fernández-Velasco, María; Ruilope, Luis M.; Ruiz-Hurtado, Gema (Frontiers in Physiology, 2021)
Cardiorenal syndrome (CRS) is a complex disorder that refers to the category of acute or chronic kidney diseases that induce cardiovascular disease, and inversely, acute or chronic heart diseases that provoke kidney dysfunction. There is a close relationship between renal and cardiovascular disease, possibly due to the presence of common risk factors for both diseases. Thus, it is well known that renal diseases are associated with increased risk of developing cardiovascular disease, suffering cardiac events and even mortality, which is aggravated in those patients with end-stage renal disease or who are undergoing dialysis. Recent works have proposed mineral bone disorders (MBD) as the possible link between kidney dysfunction and the development of cardiovascular outcomes. Traditionally, increased serum phosphate levels have been proposed as one of the main factors responsible for cardiovascular damage in kidney patients. However, recent studies have focused on other MBD components such as the elevation of fibroblast growth factor (FGF)-23, a phosphaturic bone-derived hormone, and the decreased expression of the anti-aging factor Klotho in renal patients. It has been shown that increased FGF-23 levels induce cardiac hypertrophy and dysfunction and are associated with increased cardiovascular mortality in renal patients. Decreased Klotho expression occurs as renal function declines. Despite its expression being absent in myocardial tissue, several studies have demonstrated that this antiaging factor plays a cardioprotective role, especially under elevated FGF-23 levels. The present review aims to collect the recent knowledge about the FGF-23-Klotho axis in the connection between kidney and heart, focusing on their specific role as new therapeutic targets in CRS.